TINJAUAN YURIDIS KETENTUAN DALUWARSA DALAM PENGAJUAN GANTI KERUGIAN MELALUI PRAPERADILAN TERHADAP PERKARA SALAH TANGKAP - Fitri, Uli Annisa; R, Mukhlis; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Wrong arrests are a case that often occurs in Indonesia. Literally, misunderstanding is mistaking the person in question or mistaking the person. The wrong arrest case has a huge impact on the victim and also his family. Victims of wrong arrest experience suffering physically, psychologically and materially. Often victims and also their families get negative stigma from the community who knows this. Regarding this matter, it is proper for victims of wrong arrest to receive rehabilitation and compensation. The legal basis for the court to provide compensation and rehabilitation is stated in Article 9 of Law Number 48 of 2009 concerning Judicial Powers. The regulation of the rights to compensation in the Criminal Procedure Code is a manifestation of human rights. Compensation can be filed within a maximum period of 3 (three) months from the date of excerpt or 3 (three) months after receiving a copy of the court decision with permanent legal force, this is as regulated in Article 7 paragraph (1) Government Regulation Number 92 of 2015 concerning the second amendment to Government Regulation Number 27 of 1983 concerning Implementation of the Criminal Procedure Code. However, in its implementation, there are still victims of wrongful arrests who do not receive compensation.This type of research is normative legal research which is also called doctrinal legal research. This research uses secondary data or codified scientific data. The data collection technique used in this legel research is the library research method. In this paper, the author uses qualitative data analysis wich produces descriptive data, which means explaining and concluding about the data that has been collected by the author.The result of this research is to explain that the timeframe regarding filing a claim for compensation is regulated in Article 7 paragraph (1) of Government Regulation Number 92 of 2015, but there is legal uncertainty in it so that the victim of a wrongful arrest cannot receive compensation. The author provides an ideal concept in the form of extending the time period in filing a claim for compensation as stated in Article 7 paragraph (1) of Government Regulation Number 92 of 2015 to a maximum of 6 (six) months from the date of excerpt or a copy of the court's decision with legal force is still accepted. Considering that in practice the submission of a copy of the decision took a very long time. This is done so that there is legal certainty regarding the period of time in submitting compensation for the victim of a wrongful arrest so that the victim can receive the compensation.Keywords: Expired – Claim for Compensation - Pretrial